Freedom of Conscience in Russian Empire at Beginning of 20th Century and Constitutional Reform of 1906 - S. V. Kulikov (Научный диалог, 2023)
For the first time in scientific historiography, with the involvement of previously unknown archival documents, the problem of ensuring freedom of conscience is considered when creating the Fundamental Laws on April 23, 1906, which became the first national constitution in force. It is shown that P. A. Kharitonov, A. P. Salomon and Count A. F. Heyden paid attention to this problem, that is, the authors of bureaucratic drafts of new Fundamental Laws, which by December 1905 were prepared for Emperor Nicholas II. The main one turned out to be Kharitonov’s project, considered at a Meeting of the highest ranks of the State Chancellery. In the future, the consolidation of freedom of conscience in the Fundamental Laws was facilitated by the discussion of the draft State Chancellery in the Council of Ministers under the chairmanship of Count S.Y. Witte in March 1906 and the drafting of another draft of Fundamental Laws by Professor O. O. Eichelman at the same time. It is emphasized that the controversy that arose as a result of the April Special Meeting chaired by Nicholas II among his key figures about the limits of freedom of conscience influenced the final version of the corresponding article of the Fundamental Laws established personally by the tsar. It is concluded that this version reflected the conservative-liberal nature of the views shared by the direct participants of the constitutional reform of 1906.